Identification of the Carbohydrate and Organic Acid Metabolism Genes Responsible for Brix in Tomato Fruit by Transcriptome and Metabolome Analysis - Li, Ning; Wang, Juan; Wang, Baike; Huang, Shaoyong; Hu, Jiahui; Yang, Tao; Asmutola, Patiguli; Lan, Haiyan; Qinghui, Yu (Frontiers in Genetics, 2021)
Background: Sugar and organic acids not only contribute to the formation of soluble solids (Brix), but also are an essential factor affecting the overall flavor intensity. However, the possible metabolic targets and molecular synthesis mechanisms remain to be further clarified. Methods: UHPLC-HRMS (ultrahigh-performance liquid chromatography and high-resolution mass spectrometry) combined with comparative transcriptome analysis were performed in fruits at green ripe (S1), turning-color (S2) and red ripe (S3) stages of two tomato genotypes (TM-1 (Solanum galapagense L., LA0436) and TM-38 (S. lycopersicum L. cultivar M82, LA3475)) that vary in fruit Brix. Results: The fruit Brix of TM-1 was nearly twice that of TM-38 at S3. Nevertheless, TM-1 accumulated 1.84- and 2.77-fold the L-Malic acid and citric acid in red ripe fruit (S3) compared to TM-38, respectively. D-glucose and D-fructose in TM-1 and TM-38 fruits tended to be similar at S3. Concomitantly, the sugar/organic acid ratio of TM-38 fruits were 23.08, 4.38- and 2.59-fold higher than that of TM-1 fruits at S1, S2 and S3, respectively. Among starch and sucrose (carbohydrate, CHO) metabolism (ko00500) genes, SUS (Solyc07g042550.3) and BAM (Solyc08g077530.3) were positively (r=0.885–0.931) correlated with sugar/organic acid ratio. Besides, INV (Solyc09g010080.3, Solyc09g010090.5.1), AAM (Solyc04g082090.3), 4-α-GTase (Solyc02g020980.2.1), BGL2 (Solyc06g073750.4, Solyc06g073760.3, Solyc01g081170.3), TPS (Solyc01g005210.2, Solyc07g006500.3) and TPP (Solyc08g079060.4) were negatively (r=-0.823–-0.918) correlated with sugar/organic acid ratio. The organic acid (TCA cycle) metabolism (ko00020) gene ALMT (Solyc01g096140.3) was also negatively (r=-0.905) correlated with sugar/organic acid ratio. Conclusion: Citric acid may play a more dominant role in the sugar/organic acid ratio of tomato fruit, and the contribution of both L-Malic acid and citric acid to the fruit Brix was much greater than that of D-glucose and D-fructose. Genes involved in CHO and TCA metabolism, which have a significant correlation with the sugar/organic acid ratio were considered to be the contributing factors of fruit Brix.